(untitled) (Research, Society and Development, 2021)
Although some advances have been made in recent years, studies show that health services tend to organize for a heterosexual clientele, limiting their possibilities of effective action with transgender patients. This study aimed to describe the scientific evidence on the prejudice and discrimination suffered by transgender people in health services. This is an integrative literature review study. The databases searched were BVS, LILACS, SCIELO, MEDLINE and BDENF. The period of articles published from 2011 to 2020 was defined. For data extraction, the Ursi & Galvão form was used and for data analysis, the evidence classification system, adopting the evidence hierarchy, in relation to the outline of research. The study sample consisted of seven original articles. The results were exposed and discussed in two thematic categories: Access to the health network and the types of prejudices and discrimination suffered by transgender people and Nursing care in the face of policies aimed at the LGBTQI+ public. Discriminatory care and embarrassing behaviors are among the main causes of this population to withdraw from health services, self-medicate and not adopt preventive care. It was concluded that the greatest role of nursing for LGBTQIA+ people is the guarantee of dignified and humanized assistance from the basic health sector to the high complexity sector, becoming essential for the promotion of comprehensive, qualified, humanized health, favoring the citizenship.